2022
DOI: 10.1111/dmcn.15385
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic spectrum of hereditary spastic paraplegia in Chinese children

Abstract: Hereditary spastic paraplegias (HSPs) are a group of genetically and clinically diverse inherited neurological disorders affecting around 2 to 8 in 10 0000 individuals across different populations. [1][2][3] They are characterized by progressive lower limb weakness and muscle stiffness (spasticity) due to pyramidal tract dysfunction. This lower limb weakness and spasticity can be associated with other neurological or nonneurological symptoms (complex forms, cHSP) or in relative isolation (pure forms, pHSP). 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…9,34 However, in pediatric-onset HSP cohorts, SPG54 was responsible for approximately 2% of HSP cases, which indicated that SPG54 more frequently caused HSP symptoms in early childhood. 13,14,35 Concordant to the results observed in other ethnic groups, SPG54 accounted for only 1.2% (3 out of 242) of all patients with HSP and 2% (3 out of 147) of patients with AR or apparently sporadic HSP in our Taiwanese cohort. These findings suggest that SPG54 is a rare HSP subtype and should be considered only in patients with AR or apparently sporadic HSP.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…9,34 However, in pediatric-onset HSP cohorts, SPG54 was responsible for approximately 2% of HSP cases, which indicated that SPG54 more frequently caused HSP symptoms in early childhood. 13,14,35 Concordant to the results observed in other ethnic groups, SPG54 accounted for only 1.2% (3 out of 242) of all patients with HSP and 2% (3 out of 147) of patients with AR or apparently sporadic HSP in our Taiwanese cohort. These findings suggest that SPG54 is a rare HSP subtype and should be considered only in patients with AR or apparently sporadic HSP.…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9][10][11][12][13][14] Most of the variants result in loss-of-function of the protein product (pLoF variants), including nonsense or frameshift truncating mutations, and a minor group of variants are missense mutations, including p.Y56C, p.W103R, p.R112Q, p.T186M, p.G197R, p.V220F, pR242C, pR242H, p.P269L, p.P339S, p.Q487H, p.F502S, pG510E, p.D660H, p.C683S, and p.Y699C. [7][8][9][10][11][12][13][14] Among these mutations, only p.R287* and p.D660H have been identified in more than two families. 8,15,16 Most SPG54 patients have early-onset disease, with symptoms presenting in the first decade of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, two CPT1C variants have been identified to date as the genetic cause of a pure adult‐onset autosomal dominant form of the disease, known as hereditary spastic paraplegia 73 (SPG73), which leads to a loss of independent ambulation 10–15 years after the onset of the symptoms in both men and women (Boutry et al., 2019; Hong et al., 2019; Rinaldi et al., 2015). Moreover, two other CPT1C mutations have also been detected in paediatric patients with complicated forms of HSP, one of them causing delay of speech, cortical dysplasia, seizures and hearing impairments (Wang et al., 2023). However, none of these subjects exhibited cognitive alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, Schiavoni et al 3 reported a retrospective cohort study of 47 Italian patients with HSP onset as children. Now, Wang et al 4 present a retrospective cohort study of 45 Chinese patients with a clinical diagnosis of childhood onset HSP. In the Wang et al 4 study, a genetic etiology was identified in 35 of these individuals (78%), a percentage exceeding that of many similar studies.…”
mentioning
confidence: 99%